Reversal effect of adenovirus-mediated human interleukin 24 transfection on the cisplatin resistance of A549/DDP lung cancer cells - Xu, Mingju (Oncol Rep, 2017)
Interleukin-24 (IL-24) is a tumor-suppressor gene that has been documented in human melanoma cells. IL-24 has marked antitumor activities on various types of human cancer, but its underlying mechanism remains unclear. In the present, we investigated the effects of human IL-24 (hIL-24) on the chemotherapy resistance of lung cancer cells. The cisplatin (DDP)-resistant lung carcinoma cell line A549/DDP was subjected to adenovirus-mediated transfection with the human IL-24 gene (Ad-hIL-24). The growth-inhibitory and apoptotic effects of Ad-hIL-24 on A549/DDP cells were observed, and the expression levels of AKT, phosphorylated-AKT (p-AKT) and P-glycoprotein (P-gp) were detected. Ad-hIL-24 significantly decreased the levels of p-AKT and P-gp, and effectively inhibited A549/DDP cell growth. Furthermore, A549/DDP cells exhibited a significantly increased rate of apoptosis, as well as G2/M-phase arrest, following transfection with Ad-hIL-24, and these effects were increased in cells treated with Ad-IL-24 combined with DDP when compared with those treated with Ad-hIL-24 or DDP alone. These results suggest that hIL-24 can reverse the DDP resistance of lung cancer cells, and that the associated mechanism involves the induction of apoptosis and G2/M-phase arrest through the phosphoinositide3-kinase (PI3K)/AKT signaling pathway, as well as a decrease in drug resistance through P-gp expression.